Students' Socio-scientific Reasoning to Measure Decision-Making Ability Related to Sustainable Energy Issues - Rifqi Anjar Mustika; Wirawan Fadly; Martinez David (Journal of Innovation in Educational and Cultural Research, 2025)
Along with the development of the era and technology and the increasing human population, the need for energy use is increasing. This study aims to measure students' reasoning and decision-making abilities related to socio-scientific problems. This study uses quantitative research with a cross-sectional survey research design. The research sample was determined by purposive sampling, and 26 samples were collected from class VII B at SMPN 1 Sambit Ponorogo. Measurements in this study were carried out through 2 tests: the first was a multiple-choice test, and the second was a descriptive test. The results of this study show that the Cronbach Alpha value in the form of interaction between person and item items as a whole, worth 0.72, is a "Good" level. Then, it shows the person reliability value or respondent reliability of 0.65 and item reliability or instrument reliability of 0.10. This shows that the consistency of respondents' answers is in the "good" category. Thus, this study can provide a direction for further developing more effective learning approaches and methods to improve students' abilities in dealing with complex issues.